A hemispheric decoding principle for vestibular heading perception in the posterior sylvian area - Yue Xu; Yong Gu (Proceedings of the National Academy of Sciences, 2026)
Identifying functional links between neural activity and behavioral perception is a fundamental neuroscience issue for inferring causality and means of information-decoding. Using perturbation methods, numerous studies have provided direct evidence showing that sensory information in many systems (e.g., vision) is causally read out for subjects’ perceptual choice with respect to the manipulated neurons’ preferred feature (labeled-line code). Here we report an alternative decoding principle in the visual posterior sylvian area (VPS). Specifically, VPS neurons in each hemisphere encode heading information symmetrically in terms of leftward vs. rightward preference in the earth-horizontal plane based on inertial or visual motion cues. In a heading discrimination task, correlation between neural activity and perceptual choice on a trial-by-trial basis (choice probability) was also significantly dependent on the neurons’ tuning functions. However, electrical microstimulation in VPS significantly biased macaques’ heading judgments toward the ipsilateral hemisphere, irrespective of the artificially-stimulated neurons’ encoded heading preference. This effect was observed exclusively in the vestibular but not visual condition, and in VPS but not neighboring areas. The microstimulation induced perceptual bias could be complemented by chemical inactivation manipulations. A noninvasive galvanic vestibular stimulation applied at the peripheral inner ear organs produced similar bias in the subjects’ behavioral performance, as well as activation in the central VPS. Our findings reveal a hemispheric-readout algorithm that predominates over the labeled-line code in the central vestibular system, which may constrain the way of information integration across sensory modalities.